Indonesian Islamic Intellectual Fashion Style in The Early 20th Century: Photo Narrative Analysis - Sadono, Soni; Pandanwangi, Brilindra; Maulana, Teddy Ageng; Kasputra, Danil (RSF Conference Series: Business, Management and Social Sciences, 2023)
The development of clothing began to have a variety of functions ranging from the symbol of social status to the symbol of a person’s position. Indonesia stretches from the Hindhu-Buddhist, Islam to the modern era Indonesia clothing is very dispersed and coloured by customs and culture that developed in its time. Entering the beginning of the 20th century, with the emergence of Indonesian Intellectuals as a result of the Dutch ethical politics fashion style of Indonesian to be varied. Among Indonesian Islamic Intellectuals, a similar change occurred. Robes or sarongs are often synonymous with the characteristics of a Muslim’s clothes are no longer a major symbol. The purpose of this study is to know Indonesian Islamic Intellectuals’ clothing style in the early 20th century. The method used is a historical research method consisting of 4 stages, namely heuristics, criticism, interpretation, and historiography. The study’s results found that Western fashion styles influenced the fashion styles of Indonesian Islamic Intellectuals in the early 20th century. Suits, ties, hats and shirts are the common Western clothes these people wear.